Litters effect on soil physicochemical and biological processes - Meshram, N A; Dalvi, V V; Pinjari, S S; Rathod, R R; Narkhade, S S (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out during 2016-17 to 2018-19 at All India Coordinated Research Project on Agroforestry under Dr DBSKKV, Dapoli, Maharashtra on Assessment of decomposition dynamics, microbial community and soil fertility under different trees in Alfisol. The 10 years old six tree species, viz. Gmelina arborea, Terminalia tomentosa, Acacia mangium, Gliricidia sepium, Acacia auriculiformis and Millettia pinnata blocks were framed in a randomized block design with four replications. Significantly (P>0.05) build-up of soil fertility, microbial community and enzymes assay were found due to incorporation of Gliricidia sepium and Millettia pinnata litters and also develops bio-stability in soil which helps to maintain soil fertility. The decompositions, 0-87.35% (weight loss) were recorded and overall decomposition dynamics of litters species in soil trend was, viz. T4>T6>T2>R1>T3>T5. Significantly higher improvement in microbial C: N ratio of soil was recorded by Gliricidia sepium (9.14) and Millettia pinnata (8.99). The higher microbial communities (bacteria, actinomycetes, fungi) and enzyme assay (dehydrogenase, acid and alkaline phosphatase activities) were recorded by Gliricidia sepium followed by Millettia pinnata which helps for developing biological fertility of soil. Most of the trees are nitrogen fixing species, the higher development and restoring of soil fertility by indigenous Gliricidia sepium and Millettia pinnata species and these species could be used to more suitable for looking block plantation, bund plantation, alley cropping, development of agroforestry and subsequently could be used as a source of nutrients by directly or in-situ litter decomposition in soil in a Tropical Zone.